2015
DOI: 10.1088/0004-637x/815/2/111
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Games Between a Planet and Its Host Star: The Key Role of Topology

Abstract: Magnetic interactions between a star and a close-in planet are postulated to be a source of enhanced emissions and to play a role in the secular evolution of the orbital system. Close-in planets generally orbit in the sub-alfvénic region of the stellar wind, which leads to efficient transfers of energy and angular momentum between the star and the planet. We model the magnetic interactions occurring in close-in star-planet systems with three-dimensional, global, compressible magneto-hydrodynamic numerical simu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
134
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(140 citation statements)
references
References 67 publications
4
134
0
Order By: Relevance
“…However, these percentages fluctuate significantly in time. Such a complex field structure in space and time likely affects the SPMI expected in these close-in systems (Cuntz et al 2000;Ip et al 2004;Strugarek et al 2015).…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these percentages fluctuate significantly in time. Such a complex field structure in space and time likely affects the SPMI expected in these close-in systems (Cuntz et al 2000;Ip et al 2004;Strugarek et al 2015).…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Furthermore, we find that the energy in the dipole component of the magnetic field varies substantially in time. All of these factors affect star-planet magnetic interactions (Strugarek et al 2015) and the inferences we make from such interactions (Vidotto et al 2010). …”
Section: Discussionmentioning
confidence: 96%
“…In this case, the line connecting the star and the planet would not be anchored at the substellar point, but would instead be shifted to a different stellar longitude and/or latitude. Finally, we note that transfers of energy between the star and the planet only occur when the planet is orbiting within the stellar Alfvénic surface (Strugarek et al 2015). Therefore, understanding the realistic distribution of stellar wind particles and magnetic fields are of utmost importance to model and quantify star-planet interactions (Vidotto et al 2014).…”
Section: Understanding the Non-detectionmentioning
confidence: 91%
“…The literature on possible correlations between planetary orbital phase and stellar activity is abundant but inconclusive (e.g., Lanza et al 2011;Lecavelier des Etangs et al 2012;Pillitteri et al 2011Pillitteri et al , 2015. On the other hand, theoretical and numerical models (Lanza 2009;Cohen et al 2011;Matsakos et al 2015;Strugarek et al 2015) have long suggested that magnetic star-planet interaction intermediated by reconnection events could release energetic particles that would travel toward the star, triggering potentially measurable activity enhancement events (but see, e.g., Lanza 2012). Very recently, France et al (2016) found tentative evidence for star-planet interaction from the variation of several FUV lines (NV, CIV, SiIV).…”
Section: Introductionmentioning
confidence: 99%
“…These models have used available ZDI maps or low-order idealized magnetic fields to study and scale stellar massloss rates and stellar spindown with stellar age and rotation periods, as well as to characterize the coronae and winds of planet-hosting stellar systems (e.g., Matt et al 2012;Vidotto et al 2014;Matsakos et al 2015;Réville et al 2015;Strugarek et al 2015), while they were not calibrated by solar input parameters and solar magnetogram data. Instead, some of the models have adopted an idealized "fiducial" solar case, which is represented by solar mass, radius, rotation period, and a dipole magnetic field.…”
Section: Introduction the Zeeman-doppler Imagine (Zdi) Techniquementioning
confidence: 99%